The Impact of Covid-19 on Learning System Toward Quality Education: The Future of Global Education Outlook - James Kalimanzila; Lwitiko Gladson Mwaikuju; Girindra Putri Ardana Reswari (JETL (Journal of Education, Teaching and Learning), 2021)
The purpose of this study is to analysis the impact and challenges of covid-19 on learning system towards quality education. Currently, the World is facing pandemic COVID-19 which was experienced and appeared first in Wuhan-China around the end of 2019, it spread rapidly in the World. The COVID-19 pandemic has extraordinary impacts on education, economy, and other many sectors. However, the impacts will not only face and disturb only education sector, it will face other sectors including the future of work, healthcare, culture, economic, human relation among others. This paper collected data using qualitative method based on secondary information collected from various sources such as use of social media as document analysis methods, published and unpublished articles, newspapers, books, and reports of various education organizations, Universities sites and student forums. In this paper, the authors have analyzed the impact of the COVID- 19 on learning system.